1997
DOI: 10.1037/0022-006x.65.1.79
|View full text |Cite
|
Sign up to set email alerts
|

What is a reasonable weight loss? Patients' expectations and evaluations of obesity treatment outcomes.

Abstract: Expert panels and governmental guidelines now recommend that obese persons seek modest (i.e., "reasonable") reductions in body weight rather than striving for "ideal" weights. Little is known, however, about patients' views of what is a "reasonable" weight loss. This study assessed patients' goals, expectations, and evaluations of various outcomes before, during, and after 48 weeks of treatment. Before treatment, 60 obese women (99.1 +/- 12.3 kg; body mass index of 36.3 +/- 4.3 kg/ m2) defined their goal weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
430
4
28

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 471 publications
(488 citation statements)
references
References 26 publications
26
430
4
28
Order By: Relevance
“…Our findings, however, are consistent with the results of several other clinical trials, which found modest positive, if any, relationships between participants' expected and achieved weight losses 4,5,10 and no relationship between failure to meet expectations and attrition. 1 This study found that the intensity of the therapy provided did not appear to influence weight loss expectations or goals to a significant degree. Participants appeared to come to treatment with predetermined expectations and goals, which they did not modify in response to being assigned to different therapies or told to expect a loss of only 5-15% of initial weight.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Our findings, however, are consistent with the results of several other clinical trials, which found modest positive, if any, relationships between participants' expected and achieved weight losses 4,5,10 and no relationship between failure to meet expectations and attrition. 1 This study found that the intensity of the therapy provided did not appear to influence weight loss expectations or goals to a significant degree. Participants appeared to come to treatment with predetermined expectations and goals, which they did not modify in response to being assigned to different therapies or told to expect a loss of only 5-15% of initial weight.…”
Section: Discussionmentioning
confidence: 66%
“…[1][2][3][4][5] The losses they expected after 1 year of behavioral 19,20 There was a small positive relationship between participants' expected and achieved weight losses at week 26. Thus, participants with higher expectations lost more weight in the first 6 months of treatment.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations